14a+-93=49+57a

Simple and best practice solution for 14a+-93=49+57a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14a+-93=49+57a equation:


Simplifying
14a + -93 = 49 + 57a

Reorder the terms:
-93 + 14a = 49 + 57a

Solving
-93 + 14a = 49 + 57a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-57a' to each side of the equation.
-93 + 14a + -57a = 49 + 57a + -57a

Combine like terms: 14a + -57a = -43a
-93 + -43a = 49 + 57a + -57a

Combine like terms: 57a + -57a = 0
-93 + -43a = 49 + 0
-93 + -43a = 49

Add '93' to each side of the equation.
-93 + 93 + -43a = 49 + 93

Combine like terms: -93 + 93 = 0
0 + -43a = 49 + 93
-43a = 49 + 93

Combine like terms: 49 + 93 = 142
-43a = 142

Divide each side by '-43'.
a = -3.302325581

Simplifying
a = -3.302325581

See similar equations:

| -10=8-x*7 | | -21=7u+7(u-7) | | 3(6z+7)+10z+45=180 | | 4x^2-7x-57=0 | | (2x-30)=45 | | (x^2-1)=0 | | w-16=-3 | | x+(x+4)=50 | | 4x-19=13x-1 | | 2(x-6)=7 | | 3(6z+7)10z+45=180 | | 2/3(3x+1)=5 | | -1.25+0.5x=0 | | 9x-7=12x-4 | | 3x*3y= | | 20+8(a-11)=-12 | | 9x-7=12-4 | | x^2+8xy+16y^2-4x-16y+7=0 | | -3(2x+3)=-6x+9 | | f(-1.5)=3x^2-6x+3 | | x-11(13+4x)=-3(5-9x)+2 | | 3x+2=9x+6 | | (x-3).4=8 | | 8(3x-2y)+4[(-3x)+4y]= | | 5x-4=8x+5 | | 2.35(4x-4)=-2+10x+12 | | x+23=69 | | 5n-3[n-5]=13 | | 11x+3=9x-11 | | Y-13=-45 | | 4-x=4(x+2) | | (3p-6)+90= |

Equations solver categories